The relationship of adversity quotient and learning environment with self-directed learning - Fatma Sri Kumala Dewi; Daharnis Daharnis (International Journal of Applied Counseling and Social Sciences, 2021)
Self-directed learning is where individuals learn on an initiative without expecting the help of others to achieve their learning goals. However, it was found that students did not want to learn directly, did not have the initiative in doing assignments, rarely used existing books, did not take advantage of school facilities and some students  often cheated on their friends' assignments. This is caused by various factors such as adversity quotient and learning environment.This study aims to analyze the relationship between adversity quotient and learning environment with self-directed learning. This study uses a descriptive correlational quantitative method. The research sample was students of class X and XI of SMA Negeri 13 Padang totaling 249 students, taken using a proportional random sampling technique. This study uses the adversity quotient instrument, learning environment, and self-directed learning. Data were analyzed by simple regression and multiple regression.The results of this study indicate that on average the adversity quotient is in the high category, the learning environment is in a good category, the self-directed learning is in a good category, there is a positive and significant relationship between the adversity quotient and self-directed learning, between the learning environment and self-directed learning, and between adversity quotient and learning environment with self-directed learning.